Exposure to Second-Hand Smoke in Homes and Respiratory Symptoms Among Non-Smoking Adults in Depok, Indonesia 2025 - Ali, Faraz; Hartono, Budi (Journal of Indonesian Health Policy and Administration, 2025)
Second-hand smoke (SHS) exposure in the home environment has become a public health emergency, especially in countries with very high smoking rates, such as Indonesia. SHS exposure has already presented evidence of symptoms of the respiratory category, like a cough and shortness of breath. This study aimed to assess the association between exposure to SHS at home and the presence of respiratory symptoms among non-smoking adults in Depok, Indonesia. Convenience sampling was adopted for enrolling 108 non-smoking adults aged 18-30 who were jointly exposed to SHS in their homes for a cross-sectional study. Data aggregations of gatherings were performed using a standardized, interviewer-structured questionnaire of symptoms of the respiratory category, which is cough and shortness of breath. Descriptive statistics were used to sum up participant characteristics, and the correlation of SHS frequency and location with occurrences of the duration of the respiratory symptoms was tested using the Chi-square test. The study findings indicated a statistically significant correlation between SHS exposure in particular locations of residence (bedroom, kitchen, and living room) and self-reported frequency of shortness of breath (χ² = 59.02, p = 0.00001) and coughing (χ² = 53.94, p = 0.000168). Our study, therefore, suggests that household SHS exposure has a strong correlation with shortness of breath and coughing in non-smoking adults. The study calls for smoke-free home policies and greater public health awareness of the risk of SHS exposure.